Effect of Residual Stress on the Mechanical Properties of FSW Joints with SUS409L - Yeong-Seok Lim; Sang-Hyuk Kim; Kwang-Jin Lee (Advances in Materials Science and Engineering)
This study was performed to investigate both the residual stress distribution and the effect of the residual stress formed at the welding region on the mechanical properties of the friction stir welded joints with 409L stainless steel sheets. Residual stress measurement with hole-drilling method; mechanical property evaluation including tensile test, Charpy impact test, and fatigue test; and microstructure observation were conducted. It has got no residual stresses to speak of at the center region of the stir zone because the stored stresses are released in the process of the dynamic recrystallization, while a small quantity of compressive residual stresses is formed at the surface region of the stir zone because of strong compression reaction by the tool shoulder. A considerable amount of compressive residual stresses is formed at the thermomechanical affected zone because of the synergy between the thermal expansion due to the heat conduction from the stir zone and mechanical compression by the tool. The formation of residual stresses shows a similar tendency between the advancing side and the retreating side. Both the mitigation of residual stress in the stir zone and the formation of compressive residual stress in the thermomechanical affected zone contribute to the improvement of the mechanical properties of the friction stir welded joints.